New Approach for Providing Adaptable Curriculum Enrichment through Teaching-Learning and Evaluation - Munje, Ravindra; Rakibe, Priya; Nichit, Vikrant; Dudhekar, Anup; Shewale, Yogita (Journal of Engineering Education Transformations, 2025)
Post-pandemic, the perspective -pof the stakeholders of the education industry has changed considering online teaching learning and evaluation. Most of the stakeholders feel that a hybrid learning methodology can be adapted for multiple reasons. However, designing a framework for hybrid teaching-learning and evaluation is not easy. In this paper, an attempt is made to propose one such approach for implementing a hybrid teaching-learning and evaluation mechanism. First of all, a survey of the students was conducted to understand their opinion about the type of teaching-learning process. Then a strategy is suggested where theory sessions will be conducted online and lab sessions will be conducted in an offline (face-to-face) manner. Further, the implementation strategy, teaching-learning tools, feasibility, applicability, and challenges associated with this are discussed. The successful implantation of the suggested teaching-learning and evaluation method can be a promising solution for accommodating on-campus and off-campus learners.